Burnout syndrome among intensive care nurses - Javorac Jovan M.; Živanović Dejan B.; Knežević Jasmina D. (Srpsko lekarsko drustvo, 2019)
Introduction: Professional burnout is a complicated state of mental, emotional and physical exhaustion, which mainly occurs among participants of so-called "helping professions". Regardless that intensive care units (ICU) have been recognized as one of the most stressful working environment in contemporary nursing, the burnout syndrome in the nursing profession is still under-investigated and neglected academic term in the scientific literature of Serbia and the surrounding countries. Aim: The aim of this study was to assess the incidence of professional burnout among the intensive care unit (ICU) nurses, by using the inventory based on Freudenberger Burnout Scale. Subjects and methods: This cross-sectional study included 71 nurses who were employed in intensive care units of surgery, urology, internal medicine, pediatrics, gynecology, obstetrics, and otorhinolaryngology departments in University Hospital Center "Dr. Dragiša Mišović", which is one of five University hospitals in Belgrade, Serbia, in July of 2017. Results: The statistical analysis of the data obtained in this study showed alarming results-burnout syndrome affected approximately one-third of the observed subjects, in form of manifested or severe job burnout. In the same time, another third of subjects were classified in the category of burnout candidates. Conclusions: Burnout incidence in observed sample exceeds the mean incidence of job burnout among nurses in other European countries that has been reported in the literature. Notwithstanding some limitations of this study (non-standardized questionnaire that was used in this study and relatively small sample of study participants from only one health care institution), the authors strongly believe that the obtained results clearly indicate necessity of further research into the problem of burnout in the nursing profession.